Epistemology of epidemiology: the case of Ungdata - Ida Hydle (Norsk Forening for Epidemiologi, 2019)
One of the most significant epidemiological tools for the perceived truth about contemporary Norwegian youth is in Ungdata, Youth Data. This is a continuous online-based survey grounded upon several and varying investigations of youth in Norwegian high schools, now extending to primary schools as well. The knowledge bases, epidemiological practices, technicalities, economic premises for the work and also data publishing is handled by social scientists at Norwegian Social Research, NOVA, located at Oslo Metropolitan University. State bureaucracies, e.g. ministries and directorates, municipalities etc. can ask for investigations and overviews. NOVA has an annual income for running the Youth Data through the Norwegian Directorate of Health of 3,3 mill. NOK (2018). The Youth Data registry has become a leading force in opinions, policies, polities and resource allocations for youth at municipal and state levels for several intended purposes. Based upon NOVA reports, media comments and interviews this article reflects upon some theoretical and methodological approaches to this unique epidemiological tool concerning youth, health and welfare. Questions arise such as: Is epidemiology a taken for granted neutral and objective kind of knowledge? Should there be ethical concerns for youth and their researchers as creators of knowledge, theory and policy - other than the normal ethical rules of scientific conduct?